Hypoxia, RONS and energy metabolism in articular cartilage - Fermor, Beverley (2010)
OBJECTIVE: Increased pro-inflammatory cytokines and reactive oxygen and nitrogen species (RONS) occur in osteoarthritis (OA). Oxygen tension can alter the levels of RONS induced by interleukin-1 (IL1). RONS such as nitric oxide (NO) can alter energy metabolism. The aim of this study was to determine if oxygen tension alters energy metabolism, in articular cartilage, in response to IL1 or NO and to determine if cell death occurred. DESIGN: Porcine articular chondrocytes were incubated with IL1 or the NO donor NOC18 for 48 hrs in either 1, 5 or 20% O(2). ATP levels were measured and immunoblots for AMPK were done. Protein translation was measured by S6 activation. Senescence and autophagy were determined by increased caveolin or conversion of LC3-I to LC3-II respectively. RESULTS: 1% O(2) significantly reduced ATP levels compared with 20% O(2). 5% O(2) significantly increased ATP levels compared with 20% O(2). 1% O(2) significantly increased pAMPK protein expresion compared with 5 or 20% O(2). Oxygen tension had no effectcs on pS6, caveolin or LC3-II levels. IL-1 induced NO production was significantly reduced with decreased oxygen tension, and significantly reduced ATP levels at all oxygen tensions, but pAMPK was only significantly increased at 5% O(2). IL1 significantly reduced pS6 at all oxygen tensions. IL-1 had no effects on caveolin and significantly increased LC3-II at 20% O(2) only. NOC18 significantly reduced ATP levels at all oxygen tensions, and significantly increased pAMPK at 5% O(2) only, and significantly decreased pAMPK at 1% O(2). NOC18 significantly reduced pS6 at 1% O(2) and significantly increased caveolin at 5% O(2), and LC3-II at 1% O(2). CONCLUSION: Our data suggest 5% O(2) is optimal for energy metabolism and protective to some effects of IL1 and NO. NO has the greatest effects on ATP levels and the induction of autophagy at 1% O(2).